Spatial mapping of collagen content and structure in human intervertebral disk degeneration. Issue 4 (2nd November 2020) - Zeldin, Lawrence; Mosley, Grace E.; Laudier, Damien; Gallate, Zachary S.; Gansau, Jennifer; Hoy, Robert C.; Poeran, Jashvant; Iatridis, James C.
Abstract: Collagen plays a key structural role in both the annulus fibrosus (AF) and nucleus pulposus (NP) of intervertebral disks (IVDs). Changes in collagen content with degeneration suggest a shift from collagen type II to type I within the NP, and the activation of pro‐inflammatory factors is indicative of fibrosis throughout. While IVD degeneration is considered a fibrotic process, an increase in collagen content with degeneration, reflective of fibrosis, has not been demonstrated. Additionally, changes in collagen content and structure in human IVDs with degeneration have not been characterized with high spatial resolution. The collagen content of 23 human lumbar L2/3 or L3/4 IVDs was quantified using second harmonic generation imaging (SHG) and multiple image processing algorithms, and these parameters were correlated with the Rutges histological degeneration grade. In the NP, SHG intensity increased with degeneration grade, suggesting fibrotic collagen deposition. In the AF, the entropy of SHG intensity was reduced with degeneration indicating increased collagen uniformity and suggesting less‐organized lamellar structure. Collagen orientation entropy decreased throughout most IVD regions with increasing degeneration grade, further supporting a loss in collagen structural complexity. Overall, SHG imaging enabled visualization and quantification of IVD collagen content and organization with degeneration. There was an observed shift from an initially complex structure to more uniform structure with loss of microstructural elements and increased NP collagen polarity, suggesting fibrotic remodeling. Abstract : Second Harmonic Generation (SHG) Imaging of human IVDs at multiple degenerative levels was used to quantify changes in collagen content and structure. Analysis demonstrated changes in SHG signal intensity and entropy that indicate fibrosis and loss of collagenous structural complexity with IVD degeneration.